Incidental learning of faces during threat: No evidence for enhanced physiological responses to former threat identities - Schellhaas, Sabine; Schmahl, Christian; Bublatzky, Florian (Neurobiology of learning and memory, 2023)
Remembering an unfamiliar person and the contextual conditions of that encounter is important for adaptive future behavior, especially in a potentially dangerous situation. Initiating defensive behavior in the presence of former dangerous circumstances can be crucial. Recent studies showed selective electrocortical processing of faces that were previously seen in a threat context compared to a safety context, however, this was not reflected in conscious recognition performance. Here, we investigated whether previously seen threat-faces, that could not be remembered, were capable to activate defensive psychophysiological response systems. During an encoding phase, 50 participants with low to moderate levels of anxiety viewed 40 face pictures with neutral expressions (6 s each), without an explicit learning instruction (incidental learning task). Each half of the faces were presented with contextual background colors that signaled either threat-of-shock or safety. In the recognition phase, all old and additional new faces (total of 60) were presented intermixed without context information. Participants had to decide whether a face was new or had been presented previously in a threatening or a safe context. Results show moderate face recognition independent of context conditions. Startle reflex and skin conductance responses (SCR) were more pronounced for threat compared to safety during encoding. For SCR, this differentiation was enhanced with higher levels of depression and anxiety. There were no differential startle reflex or SCR effects during recognition. From a clinical perspective, these findings do not support the notion that perceptual biases and physiological arousal directly relate to threat-associated identity recognition deficits in healthy and clinical participants with anxiety and trauma-related disorders.
Online verfügbar: 11. Oktober 2023, Artikelversion: 31. Oktober 2023
Gesehen am 24.07.2024